2021
DOI: 10.4103/aam.aam_11_20
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Transdermal Nitroglycerine Patch and Oral Nifedipine in Preterm Labor

Abstract: Background: Currently, the main goal for the use of tocolytic therapy is to delay the birth so as to allow the use of corticosteroids for accelerating fetal lung maturity and maternal transfer to a tertiary care center and thereby reducing neonatal morbidity and mortality. Aims and Objectives: The aims amd objectives were to compare the safety and efficacy of transdermal nitroglycerine patch with oral nifedipine as a tocolytic agent to arrest preterm la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
5
1
Order By: Relevance
“…Comparison of cervical dilatation at the time of reporting for the study showed that the p value is >0.05 indicating that there is no significant difference in cervical dilatation at the time of reporting in both the study groups. In the study by Kaur P et al (2021) [16], found different results from our study. At >3 cm cervical dilation the mean prolongation of pregnancy in NTG group was 2.11±0.32 days whereas in nifedipine group it was 3.6±1.97 days.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparison of cervical dilatation at the time of reporting for the study showed that the p value is >0.05 indicating that there is no significant difference in cervical dilatation at the time of reporting in both the study groups. In the study by Kaur P et al (2021) [16], found different results from our study. At >3 cm cervical dilation the mean prolongation of pregnancy in NTG group was 2.11±0.32 days whereas in nifedipine group it was 3.6±1.97 days.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed results were comparable in both groups, with no statistical significance. Studies by Kaur et al [ 19 ], Jamil et al [ 22 ], and Dhawle et al [ 16 ] also reported that low birth weight was the most common neonatal outcome in both groups. There was no statistical significance in neonatal outcomes in either group in any of the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 95%
“…The most common adverse effect in our study in the nitroglycerine group and the nifedipine group was headache (41.5%) and tachycardia (33.8%), respectively. A study done by Kaur et al [ 19 ] reported that the most common side effect observed in the nitroglycerine group was headache in 42% of women. While the most common side effect in the nifedipine group was tachycardia, observed in 28% of women.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the importance of delaying preterm delivery through tocolysis, allowing sufficient time for the administration of the full course of antepartum steroids. In addition, delaying delivery facilitates in-utero transfer to a tertiary care center, where neonatal care is optimal, further enhancing the chances of favorable outcomes for both the mother and the newborn [5].…”
Section: Introductionmentioning
confidence: 99%